Analisis pengaruh gaya komunikasi kepala sekolah dan kompensasi terhadap kinerja guru tidak tetap (GTT) di SD Negeri Jekulo - Annisa Setiyana (COLLASE (Creative of Learning Students Elementary Education), 2023)
This research is motivated by the gap that occurs between civil servant teachers and non-civil servant teachers in the field. Communication by school principals to GTT teachers is sometimes different from PNS teachers. The same goes for the wages you receive. The importance of providing the right compensation will motivate GTT to continue working professionally and give their best performance. And accompanied by smooth communication between GTT and school principals and PNS teachers, it will have a very good impact on improving the quality of education in schools. Based on this, the formulation of the problem in this study is "How do the effects of school principal communication and multiple compensation on the performance of non-permanent teachers (GTT) in public elementary schools in Jekulo sub-district, Kudus district?". The purpose of this study, among others, is to analyze the influence of the principal's communication style and multiple compensation on the performance of non-permanent teachers (GTT) in public elementary schools in the Jekulo sub-district, Kudus district. To realize this effort, the researcher made observations in the field in the form of a questionnaire which was filled in directly by the GTT who was the research sample. From a population of 135 non-permanent teachers in the Jekulo District, 100 teachers were taken as a sample. After obtaining the data, the researchers processed it using descriptive statistical data analysis methods, instrument tests, and classical assumption tests. After that, hypothesis testing was carried out which consisted of the f test, the coefficient of determination, and multiple linear regression analysis. The results of the study show that based on the regression equation it is seen that the coefficient of the communication and compensation indicator variable is positive, this means that the increase in respondents' responses to communication and compensation can result in an increase in teacher performance. Based on the calculation of the F test, it is known that the significant value for the effect of simultaneous communication and compensation on teacher performance is 0.000 <0.05 and the calculated F value is 32.670 > F table 2.698, so it can be concluded that there is an influence of the principal's communication and simultaneous compensation on teacher performance not permanent in Jekulo District.Keywords: principal communication, compensation, teacher performance.